Relasi Sosial Masjid Baitul Falah dengan Gereja Bethel Indonesia (GBI) Rock di Surabaya - Pamungkas, Jati; Anggana, Bisma Dwi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2019)
The relation between Islam and Christianity will be always interesting to study due to the dynamics of interreligious conflicts and harmony between the two. The Bethel Indonesia Rock Church and the Baitul Falah Mosque have succeeded in establishing harmonious relations providing an example of civic harmony and equality. The Muslim-Christian network between the Baitul Falah Mosque and Bethel Rock Church in Surabaya has succesfully depicted the importance of interreligious relations, particulary between Muslims and Christians. These two places of worship have engaged in interreligious dialogue. This article attempts to examine the form of interreligious dialogue between GBI Rock and Baitul Falah Mosque, contributing to the presence of harmony between Muslim and Christians. The main conclusion of this article suggested that the two places of worship have been undertaking a dialogue of life by mutually taking care of each other on the basis of mutual trust. Through a life experience and proximity they have been succesfully developing cooperation as well as maintaining good relations and interreligious harmony.Keywords: Muslim-Christian Relations, Baitul Falah Mosque, Indonesian Bethel Church